A Pilot Study of Introductory Motivational Interviewing Training for Supported Employment Case Managers - Manthey, Manthey (International Journal of Psychosocial Rehabilitation, 2014)
Purpose: To conduct an initial pilot study to determine if introductory motivational interviewing will lead to initial know- ledge and attitudinal shifts within case-managers who work in an employment focused setting. Method: Using a pre-post design, 20 participants attending an introductory MI training filled out a questionnaire meant to assess an individual’s general knowledge of motivational interviewing and an individual’s attitudes about how to work with individuals attempting to gain employment. Results: There were statistically significant improvements in motivational interviewing knowledge and attitude shifts about how to work with individuals attempting employment. Conclusion: Introductory MI training may be an important initial step in an overall implementation effort to integrate mo- tivational interviewing in employment rehabilitation contexts. In other words, initial training may open the door for the more in-depth skill building efforts required to adequately build and sustain counselor skills in MI by helping counselors first shift their attitudes about how they work with individuals seeking employment